Collaboration between Islamic Religious Education Teachers and Shadow Teachers in Shaping the Character of Slow-Learning Students at Mrican 01 Elementary School, Kediri City - Sulistiyani, Sulistiyani; Zaenal Arifin; Ahmad Badi' (Scidac Plus, 2026)
This study aims to determine the form of synergy, dependency, responsibility, communication patterns and expertise between Islamic Religious Education teachers and Shadow Teachers in shaping the character of slow-learning students at Mrican 01 Elementary School, Kediri City. This study uses a qualitative research type, with a case study approach. Data collection instruments include interviews, documentation and observation. The subjects in the study were the principal, homeroom teacher, Islamic Religious Education teachers, shadow teachers, regular students, students and parents of slow learners. The data analysis techniques used are data reduction, data presentation and data verification. The results of the study show: 1) The form of synergy between Islamic Religious Education teachers and shadow teachers by conducting planning and coordination as well as joint evaluation in developing appropriate learning strategies; 2) The form of dependency between Islamic Religious Education teachers and shadow teachers by adapting related materials where the shadow teacher translates with language that is easier for slow-learning students to understand; 3) The communication pattern between Islamic Religious Education teachers and shadow teachers is collaborative, interpersonal, and continuous. With good cooperation between Islamic Religious Education teachers and Shadow Teachers, it is hoped that slow-learning students will not only be able to understand Islamic religious study materials, but also develop into individuals with noble morals, discipline, and self-confidence in everyday life.